GENETIC EVALUATION OF AROMATIC AND SUBMERGENCE TOLERANCE IN RICE (ORYZA SATIVA L.) - SHAHZAD, A; SABAR, M; ALI, Q; ABBAS, A; USAMA, M; MUBASHAR, U; ASHFAQ, M (Biological and Clinical Sciences Research Journal, 2024)
This study investigates the morphological and genetic characterization of Oryza sativa germplasm for submergence tolerance and aroma. Conducted at the Rice Research Institute, Kala Shah Kaku, the research aimed to assess the adaptability of diverse accessions for breeding high-yielding, fast-growing, flood-tolerant, and aromatic rice varieties. Key agronomic traits, including plant height, tiller number, panicle length and weight, flag leaf dimensions, and grain morphology, were measured using a Vernier caliper. Analysis of variance (ANOVA) revealed significant genetic variation among accessions. Molecular characterization using SSR markers identified RM-7481 as associated with submergence tolerance, while Aroma and Badex loci were linked to aromatic traits. The SUB1 gene, a key regulator of submergence tolerance, was characterized by its role in suppressing premature growth and conserving energy under waterlogging conditions. Yield-contributing traits were analyzed through correlation analysis, simple regression, and path coefficient analysis, highlighting panicle weight and 1000-grain weight as key determinants of yield. Spearman's correlation analysis showed that there was a positive correlation between grain quality and submergence tolerance in some accessions. Some of these accessions have both high yield potential and flood resilience. The study establishes a precise relationship between genetic composition and key agronomic traits, thus providing critical information for breeding programs. The results contribute to the development of submergence-tolerant and high-quality aromatic rice aligned with consumer preferences and market demands. Further, this study gives insights into the genetic and phenotypic diversity in rice germplasm, therefore providing good direction toward rice production improvements under flood conditions.